2016
DOI: 10.1021/acs.jmedchem.6b00264
|View full text |Cite
|
Sign up to set email alerts
|

Diving into the Water: Inducible Binding Conformations for BRD4, TAF1(2), BRD9, and CECR2 Bromodomains

Abstract: The biological role played by non-BET bromodomains remains poorly understood, and it is therefore imperative to identify potent and highly selective inhibitors to effectively explore the biology of individual bromodomain proteins. A ligand-efficient nonselective bromodomain inhibitor was identified from a 6-methyl pyrrolopyridone fragment. Small hydrophobic substituents replacing the N-methyl group were designed directing toward the conserved bromodomain water pocket, and two distinct binding conformations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
142
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 36 publications
9
142
0
Order By: Relevance
“…Supplementary Figure 6 ranks bromodomains by the stability of the combinations of hydration sites that are expected to be most easily targetable with a single ligand (displacement of W1 + W2, W3 + W4, W1 + W2 + W3, and W2 + W3 + W4), and can be interpreted as it was done here for the whole network and the individual sites. It is interesting to compare the water stabilities calculated here with the work of Crawford et al 16 . The authors systematically modified the size of the aliphatic side chain in a 6-methyl pyrrolopyridone ligand (compound 2), targeting the conserved water network, and studied how this affected the affinity of the ligand for eight different bromodomains across five families.…”
Section: General Approachmentioning
confidence: 71%
See 4 more Smart Citations
“…Supplementary Figure 6 ranks bromodomains by the stability of the combinations of hydration sites that are expected to be most easily targetable with a single ligand (displacement of W1 + W2, W3 + W4, W1 + W2 + W3, and W2 + W3 + W4), and can be interpreted as it was done here for the whole network and the individual sites. It is interesting to compare the water stabilities calculated here with the work of Crawford et al 16 . The authors systematically modified the size of the aliphatic side chain in a 6-methyl pyrrolopyridone ligand (compound 2), targeting the conserved water network, and studied how this affected the affinity of the ligand for eight different bromodomains across five families.…”
Section: General Approachmentioning
confidence: 71%
“…The authors found that two different substituents could displace W3 and W4 from their canonical location in BRD4(1) and TAF1 (2). Specifically, replacing the methyl with a trans-crotyl (compound 4 in Crawford et al 16 ) or with 1-butene moiety (compound 5) resulted in the displacement of W3 and W4 from BRD4(1) and TAF1(2) (PDB-IDs 5I88 and 5I1Q). The authors studied the effect of these substitutions on ligand affinity also in BRD4(2), CREBBP, BRPF1B, BRD9, TAF1(1), and CECR(2).…”
Section: General Approachmentioning
confidence: 99%
See 3 more Smart Citations